English: English - Ni Luh Putu Rastiti Era Agustini; Made Hery Santosa; Luh Diah Surya Adnyani (Fakultas Seni Rupa dan Desain ITB, 2021)
This research aimed to investigate undergraduate EFL students’ perception towards the use of Microsoft Word Referenceson students’ thesis and factors that influence the perception. This research used a sequential mixed method. There were 25 students from 7th semester of English Language Education, Ganesha University of Education, involved in this research.The research instruments were questionnaire and interview. The results from the questionnaires were analyzed usingmean score ideal (Mi) and standard deviation ideal (SDi), and data from the interviews were analyzed using interactivemodel analysis by Miles and Huberman. From the ideal mean score analysis, the mean score of undergraduate EFLstudents’ perception towards the use of Microsoft Word References on students’ thesis was 41.84, which was categorizedas average. This means Microsoft Word References can be used in managing citation and reference in thesis writing.Moreover, the interview result shows 11 factors that influence undergraduate EFL students’ perception towards the use ofMicrosoft Word References on students’ thesis, namely attitudes, motives, interests, expectations, novelty, motion, size,background, proximity, and time. The factors build two trends, positive and negative perceptions.